Prevalnce of dengue in the Parist of “Lagunillas”, Sucre Muicipaly, Mérida State, 2005 – 2015. (Revista Venezolana de Salud Pública, 2017)
Dengue is a viral disease that depends on interactions between environment, agent, population of hosts and vector, as well as socioeconomic, political, technical and administrative determinants. The article aims to describe the prevalence of dengue for the period 2005 to 2015 in the Lagunillas parish of the municipality of Sucre, Mérida, Venezuela. Methodology: quantitative approach, descriptive type and non-experimental longitudinal design. Results: 2947 cases of dengue were found between the years under study. The presence of dengue with signs of alarm was recorded in the last three years of the study period and for severe dengue, the highest incidence occurred in 2010 with 1,085 cases / 100,000 inhabitants, the standardized prevalence rate: 2005 13/1000 inhabitants, by 2010 28/1000 inhabitants and 2015 of 8/1000 inhabitants and the projection (2016-2025) of the cases of dengue, a relation was obtained directly proportional in the time series, as Years increase the casuistry of the disease. Conclusions: The Lagunillas parish of Mérida state presents a high prevalence of dengue, being classified as an epidemic zone. It was determined that in the years 2013-2015 the dengue with signs of alarm, has suffered an increase in its incidence, although it has not been determined the cause, it is very probable that local environmental phenomena, such as the water deficit, as well as the social context , May translate into an increase in the density of the dengue transmitter vector and an increase in the reporting of dengue cases.
Keywords: Dengue; Prevalence; Epidemiology; public health